Relasionalitas Filsafat Fondasi Interpretasi: Aku, Teks, Liyan, Fenomen - Sermada Kelen Donatus (Studia Philosophica et Theologica, 2019)
The author of the book “Relasionalitas Filsafat Fondasi Interpretasi: Aku, Teks, Liyan, Fenomen”, Armada Riyanto, CM, has the great effort to philosophize his main thought about “Relasionalitas” (Relationality) which can be stated under the title called “The Philosophy of the Relationality”. The method and the scheme the author has managed to philosophize his ideas have come out from his deepest inner heart spontaneously, intuitively and genuinely, and by numerating the ideas the author would like to express, he has elaborated the meaning of those ideas focusing on the main issues like “aku, teks, liyan, fenomen” that become the foundation for a journey of interpreting the relationality. The reader of the book is allowed to become a disciple in the journey of seeking the meaning of the text in which the author offers the starting point of the journey with the dialog between “Aku dan Teks”. The word “fenomen” is understood as the reality of the daily life formed by the process of relationality that is taking place in dialog between “Aku” as the subject and “liyan” as the subject, but in the light of author’s idea, the word “liyan” refers to the social groups who are marginalized, impoverished, powerless and voiceless people.